Erratum: ROHAN MAITY, KRISHNA CHOWLU & SUDHANSU SEKHAR DASH (2024) The current status of Henckelia peduncularis (Gesneriaceae): Taxonomy, typification, distribution and IUCN Red List assessment. Phytotaxa 644 (1): 27–34. - Maity, Rohan; Chowlu, Krishna; Dash, Sudhansu Sekhar (Phytotaxa, 2024)
N/A